Development of a high yielding E. coli periplasmic expression system for the production of humanized Fab' fragments. (17th November 2016) - Ellis, Mark; Patel, Pareshkumar; Edon, Marjory; Ramage, Walter; Dickinson, Robert.; Humphreys, David P.
Abstract : Humanized Fab′ fragments may be produced in the periplasm of Escherichia coli but can be subject to degradation by host cell proteases. In order to increase Fab′ yield and reduce proteolysis we developed periplasmic protease deficient strains of E. coli . These strains lacked the protease activity of Tsp, protease III and DegP. High cell density fermentations indicated Tsp deficient strains increased productivity two fold but this increase was accompanied by premature cell lysis soon after the induction of Fab′ expression. To overcome the reduction in cell viability we introduced suppressor mutations into the spr gene. The mutations partially restored the wild type phenotype of the cells. Furthermore, we coexpressed a range of periplasmic chaperone proteins with the Fab′, DsbC had the most significant impact, increasing humanized Fab′ production during high cell density fermentation. When DsbC coexpression was combined with a Tsp deficient spr strain we observed an increase in yield and essentially restored "wild type" cell viability. We achieved a final periplasmic yield of over 2.4g/L (final cell density OD600 105), 40 h post Fab′ induction with minimal cell lysis.The data suggests that proteolysis, periplasm integrity, protein folding and disulphide bond formation are all potential limiting steps in the production of Fab′ fragments in the periplasm of E. coli . In this body of work, we have addressed these limiting steps by utilizing stabilized protease deficient strains and chaperone coexpression. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 33:212–220, 2017